Alignment Analysis of WS 3Ci River Basin Management with Law No. 17/2019 and Integrated Water Resources Management - Fathin, Yumi Amiroh; Purnaditya, Ngakan Putu; Subekti, Subekti (Fakultas Teknik Universitas Tanjungpura, 2025)
The Banten region relies on water resources from the Cidanau-Ciujung-Cidurian Watershed but faces problems such as flooding, drought, poor coordination, mangrove forest populations that are decreasing each year, and moderately polluted river water quality. The government issued a decree to the Minister of Public Works and Housing No. 548/KPTS/M/2018 on water resources management plans to address these issues. To overcome these problems. This research analyzes the alignment of the Cidanau-Ciujung-Cidurian River Basin Water Resources Management Plan with Law No. 17 of 2019 and IWRM. The method used is a comparative analysis of the water resources management plan of the Cidanau Ciujung Cidurian River Basin with Law No. 17 of 2019 and IWRM. Based on the study's results, it was found that the WS 3Ci Water Resources Management Plan is mostly in line with the Law. However, there are misalignments, namely, not listing endangered plant and animal species. At the same time, about IWRM, there are misalignments with the 4 Dimensions of water resources management, namely fossil water, green water, and water resources sustainability aspects of global scale economic sustainability.